Human Resource Management in the Batik Industry: Evaluating the Role of Training and Development in Indonesia - Sholihin, Teguh Adhe; Fazriyani, Fanesha; Fadhilah, Amalia Rachmawati Nur; Firdaus, Shafira Maharani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The article titled Human Resource Management in the Batik Industry: Evaluating the Role of Training and Development in Indonesia